2018
DOI: 10.1002/clc.22932
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy: A systematic review of the literature

Abstract: Peripartum cardiomyopathy (PPCM) is a rare cause of heart failure. It is defined as cardiomyopathy that develops in the last month of pregnancy or within 5 months of the postpartum period without an identifiable cause. We conducted a systematic review of literature of prospective studies with a focus on echocardiographic and long-term clinical outcomes in PPCM. We searched MEDLINE and Embase up to October 1, 2017. Prospective studies (sample size ≥20) reporting all-cause mortality and follow-up duration of ≥1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…However, timely and accurate diagnosis is not without a clue to follow; as previously reported, the mean hs-CRP in control patients of the same postpartum period with diagnosed patients with PPCM varied somewhat from patients with PPCM. [ 26 ] Similarly, in our study, an elevated plasma concentration of hs-CRP was observed in patients with PPCM, and these results possibly reflected the existence of a mild chronic inflammatory process because of the emission of endotoxin or endotoxin-like materials and the following pro-inflammatory cytokines discharge, which might matter in PPCM development [ 12 , 27 ] (Table 3 ).…”
Section: Discussionsupporting
confidence: 65%
“…However, timely and accurate diagnosis is not without a clue to follow; as previously reported, the mean hs-CRP in control patients of the same postpartum period with diagnosed patients with PPCM varied somewhat from patients with PPCM. [ 26 ] Similarly, in our study, an elevated plasma concentration of hs-CRP was observed in patients with PPCM, and these results possibly reflected the existence of a mild chronic inflammatory process because of the emission of endotoxin or endotoxin-like materials and the following pro-inflammatory cytokines discharge, which might matter in PPCM development [ 12 , 27 ] (Table 3 ).…”
Section: Discussionsupporting
confidence: 65%
“…Peripartum cardiomyopathy (PPCM) is a dilated cardiomyopathy marked by systolic dysfunction occurring at the end of pregnancy or, more commonly, in the early postpartum period . Globally, incidence appears to be highest in Nigeria (up to 1 in 100 live births) and Haiti (1 in 300 live births) .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is currently a lack of large cohort studies of PPCM in China. A study involving pregnant women treated at Peking Union Medical College Hospital between January 1995 and December 2014 showed that only one maternal morbidity event was noted per 1067 deliveries [ 11 ]. Although PPCM is a rare disease, it poses a serious threat to the health of pregnant women and their newborns.…”
Section: Discussionmentioning
confidence: 99%